Challenging the Patriarchal Norms: Examining Hegemonic Masculinity in Dickinson TV Series - Andieni Rahmawati; Alfi Syahriyani (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2022)
In the 19th century, hegemonic masculinity and patriarchal system were part of the society and even became the norms that people believed and obeyed. Emily Dickinson, a female character in Dickinson series, had to deal with gender discrimination practiced by the patriarchal society, specifically hegemonic masculine figure. This research aims to investigate the hegemonic masculinity experienced by the main female character in Dickinson season 1, and how she challenged the notion of hegemonic masculinity. The writer uses descriptive qualitative method as well as the theory of hegemonic masculinity by Raewyn Connell. This study found that there were various traits of hegemonic masculinity that Emily had to face from the hegemonic masculine figure, namely authority, aggression, technical competence, and subordination of women. It also showed that the character in the series tried to challenge the hegemonic masculinity performed by her hegemonic father. The acts proved that the female character put effort in fighting againts the injustice and discrimination toward her as a woman.